Spike-Receptor Binding Domain (SRBD) Antibodies Secretion in COVID-19 Survivors and Non-Survivors Post-Pre-Endemic Vaccination - , Museyaroh; Woelansari, Evy Dyah; Kriharyani, Dwi (Folia Medica Indonesiana, 2022)
Highlights • The research this for determine the presence of immune response post-vaccine • The results of this study indicate that there are differences in immune responses, in survivors patients have higher SRBD antibody levels than non-survivors Abstract : The development of a vaccine for SARS-COV-2 began in mid-2020 with the aim of stimulating an individual's immune response against SARS-CoV-2 infection. The purpose of this study was to determine the levels of post-vaccine SRBD antibody secreted in COVID-19 survivors and non-survivors. Antibodies are considered to play a more important role in evaluating immunity because antibody tests may provide information about a person's immune status against SARS-CoV-2. The study was conducted at Husada Utama Hospital, Surabaya, Indonesia, in April – May 2021. The samples were taken prospectively with a total sample of 60 patients, consisting of 40 non-survivors and 20 survivors of COVID-19 who had received Sinovac vaccine doses 1 and 2. Examination of Sars-CoV-2 SRBD antibody was conducted by using CL series of Mindray device by means of CLIA method. The average level of antibody was assessed in each sample group and the results were subjected to the Mann Whitney test. The mean SRBD antibody level in female patients was 428.24 ± 271.25, while in male patients it was 310.40 ± 113.71 U/mL. The results of the Mann Whitney test revealed a P-Value of 0.09 > 0.05, indicating no difference in post-vaccine SRBD antibody levels between females and males, but there were differences in SRBD antibody levels in COVID-19 survivors and non-survivors with a P-Value of <, i.e. 0.00 < 0.05 There was no difference in post-vaccine SRBD antibody levels between females and males in COVID-19 survivors and non-survivors, but there were differences in post-vaccine antibody levels between COVID-19 survivors and non-survivors.